From Total Institution to Status Bloodbath: Goff man as a Comparative Researcher and Grounded Theorist - Archibald, W. Peter; Kelly, Benjamin; Adorjan, Michael (Qualitative Sociology Review, 2015)
Erving Goff man has not only had a huge impact upon his home discipline of sociology but may be its most cited, as well as best known member ever. Nevertheless, Goff man continues to be heavily criticized by his fellow sociologists for his allegedly undecipherable and sloppy methods for conducting empirical research and constructing and accumulating general theory. We demonstrate here that while some of his specific practices were intuitive and unorthodox, and perhaps not always available to Goff man himself through self-reflection, they often included systematic empirical comparisons and generalizations, and grounded, general theory. It is tragic that he apparently died lamenting that these common characteristics of his work have been so little recognized (Berger 1986). He encouraged Verhoeven (1993), among others, to rectify this, and hopefully our own eff orts here have contributed to this important, but unfinished business.